Cumulative Incidence of Functional Decline After Minor Injuries in Previously Independent Older Canadian Individuals in the Emergency Department. Issue 10 (11th October 2013) - Sirois, Marie‐Josée; Émond, Marcel; Ouellet, Marie‐Christine; Perry, Jeffrey; Daoust, Raoul; Morin, Jacques; Dionne, Clermont; Camden, Stéphanie; Moore, Lynne; Allain‐Boulé, Nadine
<x xml:space="preserve">Abstract</x> Objectives To estimate the cumulative incidence of functional decline in independent older adults 3 and 6 months after a minor injury treated in the emergency department (ED) and to identify predictors of this functional decline. Design Prospective cohort study. Settings Three Canadian teaching EDs. Participants Individuals aged 65 and older who were independent in basic activities of daily living before their injury and were evaluated in the ED for minor injuries (N = 335). Measurements Functional decline was defined as a loss of 2 or more out of 28 points on the self‐reported Older Americans Resources Services scale. Sociodemographic, mobility, and clinical risk factors for functional decline in non‐ED studies were measured at the ED visit and 3 and 6 months after the injury. Generalized linear mixed models were used to explore differences in functional decline between groups determined according to the different factors. Results The cumulative incidence of decline was 14.9% (95% confidence interval (CI) = 7.6–29.1%) at 3 months and 17.3% (95% CI = 9.7–30.9%) at 6 months. Predictors of functional decline were occasional use of a walking aid (relative risk (RR)=2.4, 95% CI = 1.4–4.2), needing help in instrumental activities of daily living (IADLs) before the injury (RR = 3.1, 95% CI=1.7–5.5), taking five or more daily medications (RR = 1.8, 95% CI = 1.0–3.2), and the emergency physicians' assessment of functional decline (RR = 2.8, 95% CI = 1.5–5.3). Conclusion Minor injuries in independent older adults treated in EDs are associated with a 15% cumulative incidence of functional decline 3 months after the injury that persisted 6 months later. Simple‐to‐measure factors such as occasional use of a walking aid, daily medication, need for help with IADLs, and physician assessment of decline may help identify independent older adults at risk of functional decline during their consultation. These results confirm the need to improve risk assessment and management of this population in EDs.